2009
DOI: 10.1016/j.ejcts.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Coronary Artery Bypass Grafting Registry Study: how well does the EuroSCORE predict operative risk for Chinese population?☆

Abstract: EuroSCORE model does not accurately predict outcomes in this group of Chinese CABG patients. Therefore, caution should be exercised when using it for risk prediction in China. Creation of a new model, which accurately predicts outcomes in Chinese CABG patients, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 16 publications
0
27
0
4
Order By: Relevance
“…Nevertheless, the results were not as disappointing as those in Western populations, regardless of discrimination or calibration. 6,11,15,24,25 The results of various validation studies of EuroSCORE performed in different countries are summarized in Table 4. 5,6,8e12,15,25e27 In Taiwan, Chen et al 15 reported an observed mortality rate of 10.6% in 801 adults patients who received primary or reoperative CABG, including both off-and on-pump CABG patients and those who underwent combined procedures during Therefore, the EuroSCORE model as well may play an important role in identification of potentially high-risk patients for some minimally invasive procedures such as transcatheter aortic valve implantation, when an adequate cut-off point is defined by more reliable population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results were not as disappointing as those in Western populations, regardless of discrimination or calibration. 6,11,15,24,25 The results of various validation studies of EuroSCORE performed in different countries are summarized in Table 4. 5,6,8e12,15,25e27 In Taiwan, Chen et al 15 reported an observed mortality rate of 10.6% in 801 adults patients who received primary or reoperative CABG, including both off-and on-pump CABG patients and those who underwent combined procedures during Therefore, the EuroSCORE model as well may play an important role in identification of potentially high-risk patients for some minimally invasive procedures such as transcatheter aortic valve implantation, when an adequate cut-off point is defined by more reliable population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac surgery is only exceptionally done when this value reaches 45 or inversely 15, the risks in such patients are however high. Additionally, the scientific observation visible in the 95% confidence limits (CL) between the predicted and the observed hospital mortalities, as in this publication by Zheng, limits inference building [1]. The 95% CL of the predicted mortality ranges from 4.2% to 7.3% while that of the observed mortality ranges from 2.3% to 4.6%.…”
mentioning
confidence: 93%
“…OPCAB was first introduced in China in 1996, 1 and Ͼ50 major cardiovascular centers across the country have routinely used the technique. On the basis of a large registration study involving Ϸ10 000 patients from 35 centers across China, 2 OPCAB accounts for Ͼ70% of all coronary artery bypass graft (CABG) surgeries done in these centers, a proportion that was Ϸ3 times as high as that reported in other populations such as the United States. 3 Unfortunately, when confronted with the growing volume, we seldom have adequate evidence from the literature.…”
mentioning
confidence: 99%